2023
DOI: 10.1002/lol2.10310
|View full text |Cite
|
Sign up to set email alerts
|

Over half a century record of limnology data from Lake Powell, desert southwest United States: From reservoir filling to present day (1964–2021)

Abstract: This 58-yr water quality dataset spans the filling of a large reservoir in an arid ecoregion. The data are contained in a series of 8 flat files and are research ready, containing 5208 unique site visits, with long-term quarterly to monthly scale data from nine sites. Data include spatially explicit profile measurements of standard limnological variables as well as discrete measurements of Secchi depth, total suspended solids, and major ion and nutrient concentrations. It also contains surface phytoplankton an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…Colorado River water temperatures (in degrees Celsius) were gathered from U.S. Geological Survey (USGS) gage 09380000 (https://www.gcmrc.gov/discharge_qw_sediment/station/GCDAMP/09380000); however, there were some instances where data from a nearby downstream gage (https://pubs.usgs.gov/ds/2007/251/) were used to model missing water temperatures in Lees Ferry. Total phosphorus and soluble reactive phosphorus (SRP) (both micrograms per liter) concentrations were measured from water samples that were collected at two locations (Glen Canyon Dam power plant draft tubes and ~20 km downstream from Glen Canyon Dam) on multiple dates in 1998 and 2022 (see Deemer et al, 2023, for detailed information). We specifically focused on phosphorus because previous work has indicated that the Lees Ferry tailwater ecosystem is strongly P‐limited (Deemer et al, 2023; Korman et al, 2021; Yard et al, 2023).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Colorado River water temperatures (in degrees Celsius) were gathered from U.S. Geological Survey (USGS) gage 09380000 (https://www.gcmrc.gov/discharge_qw_sediment/station/GCDAMP/09380000); however, there were some instances where data from a nearby downstream gage (https://pubs.usgs.gov/ds/2007/251/) were used to model missing water temperatures in Lees Ferry. Total phosphorus and soluble reactive phosphorus (SRP) (both micrograms per liter) concentrations were measured from water samples that were collected at two locations (Glen Canyon Dam power plant draft tubes and ~20 km downstream from Glen Canyon Dam) on multiple dates in 1998 and 2022 (see Deemer et al, 2023, for detailed information). We specifically focused on phosphorus because previous work has indicated that the Lees Ferry tailwater ecosystem is strongly P‐limited (Deemer et al, 2023; Korman et al, 2021; Yard et al, 2023).…”
Section: Methodsmentioning
confidence: 99%
“…Total phosphorus and soluble reactive phosphorus (SRP) (both micrograms per liter) concentrations were measured from water samples that were collected at two locations (Glen Canyon Dam power plant draft tubes and ~20 km downstream from Glen Canyon Dam) on multiple dates in 1998 and 2022 (see Deemer et al, 2023, for detailed information). We specifically focused on phosphorus because previous work has indicated that the Lees Ferry tailwater ecosystem is strongly P‐limited (Deemer et al, 2023; Korman et al, 2021; Yard et al, 2023).…”
Section: Methodsmentioning
confidence: 99%